The Effect of Proposed Training Program on the Development of Skill Performance for Non-Dominant Leg on some Football Skills - Abd Al-Rahman Al-Shamayleh; Esam Abu Shihab (My University, 2016)
This study aimed to identify the Effect of proposed Training Program on the Development of Skill performance for Non-Dominant Leg on some Football Skills (Kick the ball To further distance, Ball control for a minute, Running with ball (30m), Zigzag running with ball (25m), Accuracy of shooting and Accuracy of passing), The sample of the study consisted of (25) players who are currently the team of the Faculty of Sport Sciences at Mutah University. The researcher used the experimental method, The Sample has been way one group, The statistical measures that were used included Paired-Sample (T) Test, Kolmogorov-Smirnova, Averages and standard deviations. The results of this study showed statistically significant differences between post measurement of the Non-Dominant Leg and Dominant Leg. This was for the Non-Dominant Leg. The researcher recommends the proposed training program is accredited as a way to improve the skill of the players on the level of Non-Dominant Leg in football, especially in the early age groups.

هدفت هذه الدراسة التعرف إلى أثر برنامج تدريبي مقترح لتحسيأن الأداء المهاري للقدم غير المفضلة على بعض مهارات كرة القدم (ركل الكرة لأبعد مسافة، تنطيط الكرة بالقدم لمدة دقيقة، الجري بالكرة (30م) لأفضل زمن، تمرير الكرة على أربع أهداف صغيرة، الجري المتعرج بالكرة (25م)، تصويب الكرة على هدف مقسم)، وتكونت عينة الدراسة من (25) لاعباً، تم اختيارهم بالطريقة القصدية من منتخب كلية علوم الرياضة لكرة القدم، واستخدم الباحث المنهج التجريبي بطريقة المجموعة الواحدة، حيث تم استخدام اختبار(ت) للعينات المزدوجة واختبار لكموجروف-سميرنوف والمتوسطات الحسابية والانحراف المعياري، وأظهرت نتائج الدراسة وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α≤ 0.05) بين متوسطي الأداء البعدي لمهارات (ركل الكرة لأبعد مسافة، تنطيط الكرة بالقدم لمدة دقيقة، الجري بالكرة (30م) لأفضل زمن، والجري المتعرج بالكرة (25م) بين القدم غير المفضلة والقدم المفضلة ولصالح القدم غير المفضلة، ويوصي الباحث باعتماد البرنامج التدريبي المقترح كوسيلة للارتقاء بالأداء المهاري للاعبين على صعيد القدم غير المفضلة في كرة القدم، وخاصة في المراحل العمرية المبكرة.
أثر برنامج تدريبي مقترح لتحسين الأداء المهاري للقدم غير المفضلة على بعض مهارات كرة القدم